Understanding Gen Z at Work: the Impact of Harmonious Passion, Work Environment, and Role Clarity on Job Performance Through Job Satisfaction in Indonesia’s State-Owned Construction Sector - Rayi Kusumaningrum; Restian Dini M; Siskha Mulyasari; Agustian Budi Prasetya (Green Publisher Indonesia, 2025)
Generation Z now constitutes the largest segment of Indonesia's workforce, bringing distinct values and expectations to highly structured sectors like state-owned construction enterprises (BUMN Karya). However, performance and engagement surveys indicate Gen Z scores lower in both job satisfaction and performance compared to other generations, highlighting a critical need to understand the drivers of their workplace effectiveness. This research aims to investigate the impact of harmonious passion, work environment, and role clarity on job performance among Generation Z employees in Indonesia’s state-owned construction sector, with job satisfaction as a mediating variable. A quantitative approach was employed, using data from 265 respondents collected via online questionnaires. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was applied for analysis. The findings indicate that role clarity and work environment significantly affect job performance both directly and indirectly through job satisfaction. Harmonious passion, while not directly influencing performance, enhances job satisfaction, which in turn partially mediates its effect on performance. The research underscores the importance of fostering a supportive work environment, ensuring role clarity, and nurturing intrinsic motivation to improve job satisfaction and performance among Gen Z workers. Practical implications include recommendations for organizations to enhance communication, provide meaningful work, and create conducive working conditions to boost productivity and retention.